Estudo comparativo entre extração Soxhlet e ultrasom para determinação de hidrocarbonetos policíclicos aromáticos em sedimentos do estuário do rio Sergipe por cromatografia a gás acoplada a espectrometria de massas - Santos, Antonio Sérgio Oliveira dos (2011)
Polycyclic aromatic hydrocarbons (PAHs) are compounds that can be found in environmental compartments such as atmosphere, soil, sediment and water. Throughout bioaccumulation, they can also be incorporated into vegetables and animals tissues. They are mainly originated from anthropogenic sources such as fossil fuels and biomass burnings. Due they potential toxicity, carcinogenicity and mutagenicity, they must be carefully monitored. The main goal of this study is to compare two extraction methods (ultrasound and Soxhlet) and the optimization of a cleanup column and chromatographic conditions (GC-MS) for separation and determination of 16 polycyclic aromatic hydrocarbons (PAHs) established as priorities by the Environmental Protection Agency of the United States. Once optimized, the method was applied to evaluate HPAs in sediment samples collected in the Sergipe river estuarine system. The extracts were analyzed by GCMS, using a DB-5 capillary column, splitless injection and operating in SIM mode, with three ions being monitored for each PAH, one ion principal and two others as confirmation ions. We conducted a validation study of the methods. The analytical curves showed coefficients of determination (R2) above 0.99 for all 16 PAHs. For the ultrasound method, the average recovery obtained in two fortification levels (12.5 ng g-1 and 62.5 ng g-1) showed no significant differences, with a recovering average ranging from 74 to 125.4% and RSD <19.2% for all compounds analyzed, except for pyrene. The limits of detection and quantification by ultrasound ranged from 0.04 to 0.23 ng g-1 and 0.12 to 0.78 ng g-1, respectively, and the limits of detection and quantification by Soxhlet ranged from 0.03 to 0.3 ng g-1 and 0.11 to 1.0 ng g-1, respectively. On the other hand, the Soxhlet extraction did not show good recoveries for low molecular weight PAHs, especially naphthalene, acenaphthylene and acenaphthene, with values ranging from 9.5 to 98.4%. Therefore, the extraction method chosen for the analysis of PAHs in sediment was the ultrasound. It showed good recovery, speed, solvent and adsorbent economy and low extraction time. It also allows simultaneous extraction of several samples. The total concentrations of PAHs in the sediments studied ranged from 6.7 ng g-1 to 377.7 ng g-1 dry weight. The species found in higher concentrations were Benzo[ghi]Perylene (61.9 ng g-1), chrysene (52.7 ng g- 1), fluoranthene (47.9 ng g-1) and pyrene (34.1 ng g-1). The investigation of the PAHs sources suggests pyrogenic origin for most of the compounds.